Efficacy of Palbociclib and Endocrine Treatment in Heavily Pretreated Hormone Receptor-positive/HER2-negative Advanced Breast Cancer: Retrospective Multicenter Trial - Atakan Demir; Nil Molinas Mandel; Semra Paydas; Gökhan Demir; Özlem Er; Nazım Serdal Turhal; Sevil Bavbek; Yeşim Eralp; Pınar Mualla Saip; Emine Nilüfer Güler; Adnan Aydıner; Başak Oyan Uluç; et al. (Balkan Medical Journal, 2020)

(untitled)
Background:The synthesis of CDK4/6 inhibitors with endocrine treatment in two series of treatment has been widely accepted as the standard for patients with estrogen receptor-positive metastatic breast cancer. In spite of this, the activity of CDK4/6 inhibitors in patients with metastatic breast cancer who have progressed despite receiving multiple lines of treatment is not well understood.Aims:To report the activity and safety of a CDK4/6 inhibitor (palbociclib) in patients in whom at least three lines of treatment for ER+ metastatic breast cancer had failed.Study Design:Multicenter retrospective observational cohort study.Methods:In this retrospective observational cohort study, we included 43 patients who received palbociclib after at least three lines of systemic treatment for ER+/HER2− metastatic breast cancer.Results:The median progression-free survival in our population was 7 months (25th-75th percentile, 4-10), and the median overall survival was 11 months (25th-75th percentile, 6-19). Although there were some adverse events, palbociclib was generally well tolerated, so dose reduction was needed for only six patients (14%).Conclusion:The efficacy of palbociclib among heavily treated hormone receptor-positive/HER2− patients with advanced breast cancer was acceptable in terms of clinical benefit, and it was generally well tolerated among this population.